Examining the meaning and methodological characteristics of the systematized review label: A scoping review protocol. - Zahra Premji; Leyla Cabugos (PLoS ONE)
Introduction A large portion of published evidence syntheses (ES) do not conform to established standards. There is a growing number of reviews labeled as a "systematized review", but authors do not always identify specific methodological adaptations or specify the biases these may introduce. Objective The objective of this scoping review is to identify which methodological attributes common to evidence syntheses (ES) are implemented or referenced in published systematized reviews. It also aims to 1) identify and collate, where available, the reasons authors characterize their study as a systematized review 2) determine whether any justifications provided were based on resource constraints or research goals, and 3) describe common characteristics of systematized reviews. Inclusion criteria All articles that are titled as a systematized review, attempt a collocation and synthesis of existing literature, and include some methodology for their review process, will be included. Materials and methods A title search will be conducted for the terms "systematized" or "systematised" in proximity to the term "review" in a selection of scholarly sources that offer broad coverage of literature in many disciplines: Google Scholar, Lens, Web of Science Core Collection (Web of Science platform), Scopus (Elsevier platform), MEDLINE (Ovid platform). Screening and data extraction will be done in duplicate. Screening will be conducted in Covidence. Data extraction will be done in Google sheets. Data extraction elements will include common methodological characteristics relating to various steps of the evidence synthesis process. Descriptive, aggregate statistics, and categorization of reasons for selecting the systematized review type are the primary planned analysis for this review. Data availability This is a registered report protocol. The data collected in this research project will be made available in the Borealis repository (https://borealisdata.ca/) upon finalization of the study.